Persistent pastoralism : monuments and settlements in the archaeology of Dhofar - McCorriston, Joy, 1961- (Archaeological heritage of Oman ;, 2023)
A summary of archaeological work along the Dhofar plateau and its backslope into the Nejd of Southern Oman, this book documents survey and excavation of small-scale stone monuments and pastoral settlements.